Immunomodulatory Function of Vitamin D and Its Role in Autoimmune Thyroid Disease - Zhao, Rui; Zhang, Wei; Ma, Chenghong; Zhao, Yaping; Xiong, Rong; Wang, Hanmin; Chen, Weiwen; Zheng, Song Guo (Frontiers in Immunology, 2021)
Vitamin D is one of the most important nutrients required by the human body. It is a steroid hormone that plays an important role in regulating calcium and phosphorus metabolism, and bone health. Epidemiological studies have revealed a close correlation between vitamin D and many common chronic diseases. Additionally, vitamin D has recently been shown to act as an immunomodulatory hormone, and, accordingly, vitamin D deficiency was uncovered as a risk factor for autoimmune thyroid diseases, although the underlying mechanisms are still unknown. It is therefore necessary to disclose the role and mechanism of action of vitamin D in the occurrence and development of autoimmune thyroid diseases. This knowledge will help design intervention and early treatment strategies for patients with autoimmune thyroid diseases who present with low levels of vitamin D.